Structural properties of a new class of stellar structures in modified teleparallel gravity - Caliskan, Aylin; Zulqarnain, Rana Muhammad; Güdekli, Ertan; Siddique, Imran; Ahmad, Hijaz; Askar, Sameh (Frontiers in Astronomy and Space Sciences, 2023)
This paper explores new neutron star models based on spherically symmetric spacetime. We take into account the gravitational effects of f (T, T ) gravity in which T is the torsion and T is the trace of the energy-momentum tensor. Field equations are evaluated by incorporating the off-diagonal tetrad. We, in this paper discuss the detailed properties of compact stars candidates 4U 1538 − 52, J0437 − 4715, J0030 + 0451, 4U 1820 − 30, like energy density, pressure profiles, gradients, anisotropy, energy conditions, equation of state, speeds of sound, TOV equation, and compactification parameters. We discussed all these characteristics by using the quadratic cosmological model of f (T, T ) gravity. We use the well-famed junction equations to evaluate the unknown parameters. Detailed and comprehensive graphical analysis ensures that the model containing the anisotropic nature of stellar structures is physically acceptable, regular, and stable.